2022
DOI: 10.1175/bams-d-21-0119.1
|View full text |Cite
|
Sign up to set email alerts
|

The CORDEX-CORE EXP-I Initiative: Description and Highlight Results from the Initial Analysis

Abstract: We describe the first effort within the Coordinated Regional Climate Downscaling Experiment - Coordinated Output for Regional Evaluation, or CORDEX-CORE EXP-I. It consists of a set of 21st century projections with two regional climate models (RCMs) downscaling three global climate model (GCM) simulations from the CMIP5 program, for two greenhouse gas concentration pathways (RCP8.5 and RCP2.6), over 9 CORDEX domains at ~25 km grid spacing. Illustrative examples from the initial analysis of this ensemble are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 88 publications
1
29
0
Order By: Relevance
“…Different studies have demonstrated the accuracy of CORDEX-CORE models in providing consistent and high-resolution regional climate change projections [22] , [23] . These models have also been used to assess the impact of climate change on renewable energies [24] .…”
Section: Methodsmentioning
confidence: 99%
“…Different studies have demonstrated the accuracy of CORDEX-CORE models in providing consistent and high-resolution regional climate change projections [22] , [23] . These models have also been used to assess the impact of climate change on renewable energies [24] .…”
Section: Methodsmentioning
confidence: 99%
“…The CCS from the ESMs was generally well‐conserved by the RCMs, as they tended to present similar change rates but with some differences in specific regions. RegCM often depicted less changes than REMO—like in the case of coincident HW + DS over central and southeastern SA—whereas within the driving ESMs, NorESM1‐M—which is considered of low climate sensitivity (Giorgi et al., 2022)—and its corresponding RCMs also tended to show a more reduced pattern of changes. Recall that these high‐resolution models mainly inherit this signal from their driving data, although they can introduce some differentiated changes due to their ability to reproduce more sophisticated physical processes (Ambrizzi et al., 2018).…”
Section: Summary and Final Remarksmentioning
confidence: 99%
“…Most of the simulations indicated in this table under the "22" resolution label correspond to the CORDEX-CORE initiative (Coppola et al, 2021b;Giorgi et al, 2022;Gutowski Jr. et al, 2016;Teichmann et al, 2021), designed to provide homogeneous regional climate projections for most of the inhabited land regions using nine of the CORDEX domains (Figure 1a) at 0.22° resolution: North America (NAM), Central America (CAM), South America (SAM), Europe (EUR), Africa (AFR), South Asia (WAS), East Asia (EAS), Southeast Asia (SEA), and Australasia (AUS). Due to the high computational requirements, only three GCMs were selected to provide boundary conditions, representing high, medium, and low (HadGEM-ES, MPI-ESM-LR/MPI-ESM-MR, and NCC-NorESM, respectively) climate sensitivity in the CMIP5 ensemble at a global scale (using MIROC5, EC-Earth, GFDL-ES2M, respectively, as an alternative in some domains).…”
Section: The C3s Cordex Datasetmentioning
confidence: 99%
“…However, at an early stage in the preparation of the Working Group I (WGI) contribution to the Sixth Assessment Report (AR6) in 2019, data availability on ESGF was patchy and heterogeneous across domains. This spatial heterogeneity was partially alleviated by the CORDEX-CORE initiative (Coppola et al, 2021b;Giorgi et al, 2022;Gutowski Jr. et al, 2016;Remedio et al, 2019;Teichmann et al, 2021), providing homogeneous future regional climate projections across most domains at ~25 km resolution for a few RCMs nested into a number of selected driving GCMs. However, in spite of this massive community effort, the publicly available ensembles from the ESGF were too small in some domains.…”
Section: Introductionmentioning
confidence: 99%